Determinación de la calidad del suelo, mediante la caracterización física, química y biológica, para proponer un plan de recuperación de suelos en la comunidad sacha runa, parroquia shell, cantón mera, provincia de Pastaza - Ríos Molina, Kilmar Giovanny (2016)
It research is performed in it community of Sacha Runa of the Canton mere, province of Pastaza with it purpose of determine the characterization of the soil through it characterization physical, chemical and biological for propose a plan of recovery, is made a line base in which the 75% of them respondents, claim that it loss of soil is must to it logging of forest and the wrong use of the same; they do not use proper techniques to agricultural production, unaware of organic fertilizers, but they manifest their interest to learn to develop and implement to improve the quality of the soils. The community of Sacha Runa not has with them services basic of sewer and water drinking, in relation to the analysis physico-chemical and biological, is determined that the soils are practically neutral, possess a good amount of matter organic however not all is usable by the plants, them tables of reference of the laboratory indicates for them parameters matter organic with 15,11% , Nitrogen with 0.76 ppm, match with 4.3 cm ol / kg and potassium with 0.18 cm ol / kg, are high in relation to others soils for, pH them results gave 5,59 that means practically neutral, by what is necessary apply technical agricultural, good management of practices agricultural to improve the production and the productivity of the sector. For biological analyses such as total aerobic, molds and yeasts are in optimal conditions allowing to interchange with the basic elements with the MO that interact to provide nourishment to plants, soil remediation plan includes: training, incorporation of amendments to the soil through composting, Vermiculture rotation and crop diversification, use of organic fertilizers use of organic fertilizers that do not damage the quality of the soils.